Toll-Like Receptor and miRNA-let-7e Expression Alter the Inflammatory Response in Leishmania amazonensis-Infected Macrophages - Muxel, Sandra Marcia; Acuña, Stephanie Maia; Aoki, Juliana Ide; Zampieri, Ricardo Andrade; Floeter-Winter, Lucile Maria (Frontiers in Immunology, 2018)
Parasite recognition by Toll-like receptors (TLRs) contributes to macrophage activation and subsequent control of Leishmania infection through the coordinated production of pro-inflammatory and microbicidal effector molecules. The modulation of microRNA (miRNA) expression by Leishmania infection potentially mediates the posttranscriptional regulation of the expression of genes involved in leishmanicidal activity. Here, the contribution of TLR signaling to the miRNA profile and gene expression was evaluated in Leishmania amazonensis-infected murine macrophages. The infectivity of L. amazonensis was higher in murine bone marrow-derived macrophages from mice knockout for myeloid differentiation factor 88 (MyD88-/-), TLR2 (TLR2-/-) or TLR4 (TLR4-/-) than wild type C57BL/6 (WT). L. amazonensis infection of WT macrophages modulated the expression of 32% of the miRNAs analyzed, while 50% were upregulated. The absence of MyD88, TLR2 and TLR4 altered the percentage of miRNAs modulated during L. amazonensis infection, including the downregulation of let-7e expression. Moreover, the absence of signals mediated by MyD88, TLR2 or TLR4 reduced nitric oxide synthase 2 (Nos2) mRNA expression during infection. Indeed, the inhibition of let-7e increased levels of the Nos2 mRNA and NOS2 (or iNOS) protein and nitric oxide (NO) production in L. amazonensis-infected macrophages (4-24 h). The absence of TLR2 and inhibition of let-7e increased the expression of the arginase 1 (Arg1) mRNA but did not alter the protein level during infection. However, higher levels of the L-arginine transporters Cat2B and Cat1 were detected in the absence of Myd88 signaling during infection but were not altered following let-7e inhibition. The inhibition of let-7e impacted the global expression of genes in the TLR pathway by upregulating the expression of recognition and adaptors molecules, such as Tlr6, Tlr9, Ly96, Tirap, Traf6, Ticam1, Tollip, Casp8, Map3k1, Mapk8, Nfkbib, Nfkbil1, Ppara, Mapk8ip3, Hspd1, and Ube2n, as well as immunomodulators, such as Ptgs2/Cox2, Csf2, Csf3, Ifnb1, Il6ra and Ilr1, impacting NOS2 expression, NO production and parasite infectiveness. In conclusion, L. amazonensis infection alters the TLR signaling pathways by modulating the expression of miRNAs in macrophages to subvert the host immune responses.